DIGITAL TRANSFORMATION IN CORPORATE GOVERNANCE: IMPLICATIONS FOR ACCOUNTING TRANSPARENCY AND MANAGERIAL ACCOUNTABILITY - Loso Judijanto; Yunia Oktari (Adisam Publisher, 2025)
This study aims to analyze the implications of digital transformation in corporate governance on accounting transparency and managerial accountability using a literature review method. Digital transformation has brought fundamental changes to corporate management systems through the adoption of technologies such as big data analytics, blockchain, artificial intelligence, and cloud computing, which impact oversight, reporting, and managerial decision-making mechanisms. This literature review examines various previous studies to understand how digitalization strengthens corporate governance practices by improving information accessibility, audit efficiency, and financial data integrity. Furthermore, this study explores emerging challenges, such as cybersecurity risks, algorithmic bias, and the digital competency gap among stakeholders. The study's findings indicate that the appropriate application of digital technology in corporate governance systems can strengthen accounting transparency by improving reporting accuracy and speed, and foster managerial accountability through real-time data-based monitoring systems. However, successful implementation depends on the organization's commitment to balancing technological innovation with ethical principles in governance. Therefore, digital transformation is not merely a technological adaptation but also a process of recontextualizing governance principles, requiring strategic collaboration between technology, regulations, and business ethics.